JPEG 2000 Encryption Enabling Fine Granularity Scalability without Decryption - Zhu, Bin Benjamin; Yang, Yang; Li, Shipeng (IEEE Int. Symp. Circuits and Systems 2005, 2005)
In this paper, we propose a novel encryption scheme for JPEG 2000 (J2K) and motion JPEG 2000. A block cipher in CBC mode is used to encrypt the bitstream of each J2K code-block. The encrypted J2K codestream preserves almost the same fine granularity scalability as the original J2K codestream yet with small or negligible overhead, and has fine and near RD-optimal truncations for a large range of bitrates. The proposed scheme enables desired transcoding directly on a single encrypted codestream without decryption to fit diverse capabilities of devices and heterogeneous networks with time-varying bandwidths. Any node, trusted or not, along the delivery path is able to perform desired transcoding without sacrificing the end-to-end security of the system.